PENGARUH PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MORNING BAKERY BATAM - Santri Zulaicha; Rusda Irawati (Politeknik Negeri Bengkalis, 2016)
Abstract:Product and price are several factors which are affected consumer consideration in purchasing decision. A qualify product with affordable price will attract people’s interest. The purpose of this research is to know the effect of product and price toward purchasing decision in Morning Bakery Batam. Total sample in this research were 186 people and used non probability sampling technique, which is purposive sampling by choosing the most visited outlet:Windsor branch. Multiple Regression analysis used as data technique analysis andwas assisted by SPSS 20 software.The result shows product and price have positive and significant impact toward purchasing decision.Based on data analysis in this research, the variabels are valid and reliable. On the classic asumption testing with normal distribution, there were no heteros- kedastisitas and multikolinearitas which were happened. The reretion value for product is 61,7% besides 37,9%for the price. Key words : Price, Product, Purchasing Decision